PEMBUATAN MODEL INDIKATOR TEMPERATUR-WAKTU UNTUK MONITORING KUALITAS PRODUK UDANG DAN DAGING SAPI BEKU - Pudjihastuti, Isti; Susanti, Margaretha Tuti (Universitas Diponegoro, 2010)
Abstract Freezing is one way of preserving food for maintaining the quality before consumption. Frozen foods which are now circulating in the supermarket are not given yet a tool to monitor whether the food is never experienced thawing (melting) for some period. In the frozen product that has undergone uncontrolled thawing will increase microbial content rapidly at increasing temperature 10 0C. In this study the temperature-time estimator tool manufactured for frozen beef products and shrimp. This estimator tool consists of citric acid and blue litmus paper. The response will appear in blue litmus paper that changes the color becomes red when positioned at the undesired temperature. In this study, the temperature-time estimator tool is made from citric acid 1.1%, cotton and litmus paper packed in cellophane. The response is influenced by the position of estimator tool and this tool-time temperature estimator can be applied for frozen beef products and shrimp. Keywords: beef, frozen, indicators, shrimp